Globalization and National Development: Who Gains, Who Losses, How and Why? - AGBAENYI, Alexander Nnaemeka; AGHADIUNO, Kenneth Onyeka (Socialscientia: Journal of Social Sciences and Humanities, 2025)
In recent decades, intellectual traditions have debated the losses and benefits of globalization among big and small nations, how and why? In response, this study examines the uneven impacts of globalization on national development in different social formations and the underlying mechanisms driving and explaining these disparities. The study employed a comparative case study and document analyses, through the lens of World-System Theory to navigate. The study argues that developed countries exploit developing countries through unequal exchange and economic policies that exacerbate global inequalities. Findings reveal that while globalization has contributed to economic growth, it has also increased inequality, eroded traditional cultural practices, and contributed to social tensions. Economic and political capacities determine gains and losses in an anarchical arena shaped by national interests. Additionally, international institutions have restricted national sovereignty, leading to a backlash in some countries. To address these challenges, the study recommends strengthening social safety nets, promoting inclusive economic policies, reforming international institutions, fostering cultural diversity, and prioritizing environmental sustainability.